Analisis Penerapan Technological Pedagogical And Content Knowledge (TPACK) Dalam Pembelajaran Sejarah Kebudayaan Islam di kelas X Madrasah Aliyah - Padila, Cisia; Nelwati, Sasmi; Misra, Misra; Safni, Pela (Universitas Negeri Padang, 2024)
This research aims to analyze the application of Technological Pedagogical And Content Knowledge (TPACK) in the context of learning the History of Islamic Culture in class X Madrasah Aliyah. By considering the complexity of Islamic cultural history material and the need for technology integration in modern learning, this research explains how teachers can optimize technology, pedagogy and content knowledge to increase learning effectiveness. The research methods used include observation, interviews with teachers, and documentation. The results of the research show that teachers in class more or less different from K13. Analysis of TPACK at the teacher level proves that pedagogical and content knowledge is good, but there is room for improvement in integrating technology more effectively. It was found that teachers who can manage technology well are able to create a more dynamic and interesting learning environment for students. The conclusions of this research emphasize the importance of teacher training and professional development in terms of TPACK. Recommendations include providing adequate resources and support to help teachers overcome barriers that may arise in adopting this approach. Overall, this research provides in-depth insight into the challenges and potential of implementation